Efektivitas Video Edukasi Tuberkulosis Berbasis Keperawatan Keluarga Terhadap Pengetahuan, Sikap, dan Tindakan Pencegahan Keluarga Pasien - Yuliaty Kartika 'Ashri; Suyanto Suyanto; Elfira Husna; Fauzi Ashra; Mellia Fransiska; Asrul Fahmi; Satya Anggi Permana (Jurnal Ners, 2026)
Tuberculosis (TB) remains a major global health problem, with Indonesia ranking second among countries with the highest TB burden worldwide. Family members of TB patients are at high risk of infection; however, preventive behaviors remain inadequate, highlighting the need for innovative family nursing education. This study aimed to analyze the effectiveness of a family nursing-based TB educational video in improving knowledge, attitudes, and TB preventive practices among family members of TB patients at Siulak Gedang Primary Health Center. A quasi-experimental study with a two-group pretest–posttest control design was conducted in April 2026. Twenty-eight respondents were recruited using consecutive sampling and assigned to either the intervention group (three-episode TB educational video) or the control group (conventional education). Data were analyzed using paired t-test, independent t-test, and Mann–Whitney test. The intervention group showed significant improvements in knowledge (Δ = +3.43; p < 0.001), attitudes (Δ = +4.36; p = 0.001), and TB preventive practices (Δ = +3.07; p = 0.013). Between-group analysis demonstrated significant differences in knowledge (p < 0.001) and attitudes (p = 0.003), but not in preventive practices (p = 0.225). Family nursing-based TB educational videos effectively improved knowledge and attitudes and have the potential to serve as a technology-based community nursing intervention in primary healthcare settings.